Cyberdemocracy: a New Phenomenon in Politics and Sociological Linguistics in Spain - Sofía Mósina (Ибероамериканские тетради)
The article analyses cyberdemocracy as a new kind of politics in Spain, presents its key features and provides a comprehensive definition of cyberdemocracy on the basis of the existent ones. The phenomenon of cyberdemocracy is also analysed in the context of sociological linguistics, with a brief review of Spanish researches on the respective issue. A list of neologisms that appeared in the Spanish media discourse due to a new phenomenon is given, and a number of examples of ciberdemocracy manifestations in the social life of Spain are provided.